2021
DOI: 10.1017/s1740022821000267
|View full text |Cite
|
Sign up to set email alerts
|

Islam and the cognitive study of colonialism: The case of religious and educational reform at Egypt’s al-Azhar

Abstract: This article argues that the emerging Cognitive Science of Religion (CSR) provides a valuable new perspective on colonialism. CSR argues that humans are innately inclined towards certain types of religious belief (e.g., belief in spirit beings, belief in immortal souls) and certain types of non-utilitarian morality (e.g., belief in an obligation to care for kin, belief in an obligation to avoid ‘disgusting’ substances or behaviours). These innate inclinations underlie many religious and cultural traditions tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…4, December 2022: 91 -99 96 studies have shown that the faith in the apostles can have positive effects on the character of discipline, such as increasing the motivation, commitment, and perseverance of the students and teachers, as well as enhancing their moral and ethical standards [40], [41]. However, previous studies have also shown that the cultural values of making a prayer can vary depending on the social and political context, the local culture, and the personal interpretation of the students and teachers [42], [43]. These variations can affect the quality and quantity of the prayer, as well as the understanding and appreciation of its meaning and purpose.…”
Section: Resultsmentioning
confidence: 99%
“…4, December 2022: 91 -99 96 studies have shown that the faith in the apostles can have positive effects on the character of discipline, such as increasing the motivation, commitment, and perseverance of the students and teachers, as well as enhancing their moral and ethical standards [40], [41]. However, previous studies have also shown that the cultural values of making a prayer can vary depending on the social and political context, the local culture, and the personal interpretation of the students and teachers [42], [43]. These variations can affect the quality and quantity of the prayer, as well as the understanding and appreciation of its meaning and purpose.…”
Section: Resultsmentioning
confidence: 99%
“…See Anthony, 2020;de Blois, 2010;Hallaq, 2005;Motzki, 2002;Reinhart, 2010. 8 Nakissa, 2019Nakissa, 2021b. 9 Hallaq, 1984Johansen, 1998.…”
Section: Discussionmentioning
confidence: 99%
“…This has involved establishing the existence of global psychological diversity -showing that humans have a wide range of beliefs and normative values, and that Western liberal values are culturally unique rather than universal (Haidt, 2012;Heine, 2016;Henrich et al, 2010). As such, cognitive and statistical approaches offer much to humanistic scholarship which is critical of Eurocentrism (e.g., postcolonial scholarship) (see Nakissa, 2021b).…”
Section: Methodological Concerns Over Cognitive and Quantitative/ Statistical Approaches To Islamic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To strengthen and maintain relationships with spirit beings (e.g., God), Islam and other traditions prescribe duties of worship and sacrifice. To strengthen and maintain a common identity and form of community (e.g., umma ), Islam and other traditions prescribe distinctive shared practices (i.e., al ‐ shaʿāʾir al‐dīniyya ) such as rituals, forms of dress, and dietary norms (see Nakissa, 2021a,b). Generally speaking, premodern religious traditions value individual freedom and equality to some extent, and eschew random violence.…”
Section: Colonial‐era Muslim Policymentioning
confidence: 99%